Integration of Science, Technology, and Islamic Values to Enhance Expected Learning Outcomes in French Higher Education - Wulan, Elis Ratna; Gunawan, Heri; Fauziah, Wafi; Kratz, Frederic (Jurnal Pendidikan Islam, 2021)
Learning strategies like integrating Islamic values into learning can be applied to improve learning outcomes. Integrating Islamic values into learning science and technology provides opportunities for students to integrate science and technology with concepts and experiences in real life as Muslims so that they can feel that their learning is meaningful. This study aims to investigate the effect of learning science and technology that is integrated with Islamic values on the expected learning outcomes (ELO) of students. The learning material covers the basic material of science and technology. The population included lecturers and second-year students of the Institut National des Sciences AppliquÃ©es (INSA) Bourges France. Data were analysed using the Revised Ones Assignment Method. The results show that learning science and technology integrated with Islamic values has a significant effect on the expected learning outcomes of students. To achieve this, a minimum cost incurred by universities in France of 38 Euros was spent for six lecturers. They were assigned to ensure that students could explain education and its various terms (ELO1), the basis and scope of Islamic Education (ELO2), the objectives of Islamic Education (ELO3), Islamic Education methods (ELO4), Islamic Education material (ELO5), and Islamic Education evaluation (ELO6).